Masques & Phases - Ross, Robert Baldwin, 1869-1918 (Salt Lake City, UT : Project Gutenberg, 2006)
"Masques & Phases" by Robert Baldwin Ross is a collection of essays, criticism, and literary reflections written in the early 20th century. The work explores various themes related to art, archaeology, and the psychological effects produced by literature. Ross presents a unique perspective that intertwines humor and seriousness, offering a mosaic of thoughts that challenge traditional categorization in literature. At the start of the collection, the author dedicates the work to his former editor, expressing gratitude for the freedom he was given to explore his writing. Following the dedication, Ross introduces a piece titled "A Case at the Museum," which juxtaposes the lives and motivations of archaeologists and collectors, emphasizing the nuances of both pursuits. He introduces Professor Lachsyrma, an archaeologist with lost faith and deep intellect, who resides in a cluttered studio filled with artifacts. This opening sets the tone for a witty examination of artistic scholarship and the interplay between personal woes and professional obsessions, leading readers into Ross's intriguing literary world. (This is an automatically generated summary.)
Release date is 2006-01-24
Transcribed from the December 1909 Arthur L. Humphreys edition by David Price
Keywords: English essays; Short stories, English; English literature -- 20th century